Student correlates with interprofessional attitudes within undergraduate medical education - Jaime A. Foushee; Kirstie M. Everhart; Alexis M. Stoner; Lindsay Tjiattas-Saleski; David Redden (BMC Medical Education)
Abstract Background Interprofessional education (IPE) is defined as students from two or more professions learning together to collaborate and advance health outcomes and is a required component of osteopathic medical education. Factors that influence osteopathic medical students’ (OMS) interprofessional attitudes are currently unknown. This study sought to examine differences in interprofessional attitudes after completing an IPE didactic curriculum and identify specific student or curricular factors correlated with higher interprofessional attitudes. Methods This study utilized a two-phase longitudinal approach. During phase one, a pre/post survey was disseminated to OMS before and after exposure to a standardized IPE didactic curriculum. The survey collected demographic information, previous interprofessional exposures, and baseline interprofessional attitudes using the Interprofessional Attitudes Scale (IPAS). A Wilcoxon signed rank test was used to assess differences in pre/post IPAS scores. For phase two of the study, the survey was additionally disseminated to second, third-, and fourth-year OMS at the end of each academic year to identify student factors associated with higher interprofessional attitudes, including specialty interest and type of core rotation site for third year clinical clerkships and analyzed using a Kruskal Wallis test. Results Over two years, 628 OMS responded to the survey, with 585 providing sufficient information to calculate IPAS scores. Of these 585, responses were from 267 first, 133 second, 84 third, and 65 fourth year students (36 missing). For phase one, 74 of the 267 survey responders completed both the pre and post survey. There was no significant change in IPAS scores following participation in the IPE curriculum (mean change ± standard deviation − 2.22 ± 8.89; p = 0.13). For phase two, an overall decline in interprofessional attitudes was observed as students progressed through each year of academic training. Factors associated with statistically higher IPAS scores (p < 0.05) included age of 18–25, earlier point in academic curriculum (first year student) and completing clerkships at a non-academic core rotation site. Conclusions Despite curricular programming aimed at enhancing interprofessional competencies, it appears non-curricular factors may play a role in interprofessional attitudes. Examination of additional student factors and enhancement of longitudinal IPE programming across all four medical curricular years should be considered.